Artificial intelligence in the field of professional education and development - Cherkashyn, B. A. (My University, 2024)
In today's rapidly changing world, technological advancements demand that professionals continuously update their knowledge and skills. In this context, artificial intelligence (AI) emerges as a powerful tool capable of significantly transforming professional education and development processes. The use of AI enables not only the automation of routine tasks but also the personalization of learning, providing each student or professional with the necessary resources and support to achieve their career goals. This makes professional education more adaptive, individually focused, and aligned with the demands of the modern job market.
Keywords: artificial intelligence